Extracellular vesicles derived from starving BMSCs enhance survival of chondrocyte aggregates in grafts by attenuating chondrocyte apoptosis and enabling stable cartilage regeneration for craniofacial reconstruction. (1st March 2022) - Yuan, Pingping; Li, Zhiye; Shao, Bo; Zeng, Tian; Wu, Xiaopeng; Wang, Yinggang; Zhao, Yimin; Wu, Wei
Abstract: The improvement of cell survival in cartilage tissue engineering remains a challenge, especially for large-sized, specifically shaped cartilage grafts used in reconstructing craniofacial defects. In this study, we found that bone marrow mesenchymal stem cells (BMSCs) pre-conditioned in a starving environment enhanced the anti-apoptosis potential of co-transplanted chondrocytes, which significantly enhanced their survival rates before host nutrition was resumed. Further examination revealed that extracellular vesicles (EVs) derived from starving BMSCs played essential roles in ameliorating apoptosis and regulating autophagy of chondrocytes, thereby enhancing the survival of cultured chondrocytes. In vivo studies demonstrated that EVs derived from starving BMSCs significantly improved the survival of chondrocyte bricks, which confirmed the effects of nasal augmentation. These pre-treated chondrocyte bricks showed continuous cartilage growth in vivo and acquired chondrogenesis comparable to that following the chondrocyte-BMSC co-transplantation approach. This study provided new insights on how BMSC-derived EVs improved cartilage reconstruction in the craniofacial regions and offered a new approach for regenerating cartilaginous organs based on cell macroaggregates. Statement of significance: The use of extracellular vesicles (EVs) of mesenchymal stem cells has been considered as a promising approach in cartilage tissue engineering. In the present study, for the first time, we investigated the protective effect of EVs secreted by starving bone marrow mesenchymal stem cells (BMSCs) on chondrocytes in vitro and in vivo . The results demonstrated that EVs secreted by starving BMSCs inhibited chondrocyte apoptosis and chondrocyte autophagy through many microRNAs, thereby improving the survival of grafts. Transcriptomic analysis revealed the potential mechanisms of this protective effect. Graphical abstract: Image, graphical abstract